African independent churches in Soweto - West, Martin (Social Anthropology, 2016)
Of the estimated 6 000 African independent churches in Africa, approximately 3 000 are to be found in Southern Africa. Most of these are in the Republic of South Africa, where the history of the independent church movement goes back nearly a hundred years. The greatest concentration of independent churches in South Africa is to be found in the urban complexes round the cities of Johannesburg and Pretoria in the Southern Transvaal. Soweto, the complex of townships to the south-west of Johannesburg which houses about one million people, has about 900 of these independent churches. This study deals with independent churches in Soweto, and their relationship to their urban environment.